Hypereosinophilic syndrome manifested as eosinophilic gastroenteritis and colitis in a patient undergoing hemodialysis - Eri Amano; Taro Horino; Osamu Ichii; Satoshi Inotani; Tatsuki Matsumoto; Kazu Hamada-Ode; Yoshiko Shimamura; Kosuke Inoue; Yoshio Terada (Renal Replacement Therapy, 2018)
Abstract Background Hypereosinophilic syndrome (HES) consists of a group of disorders characterized by abnormal accumulation of eosinophils in the blood or peripheral tissues, independent of known secondary causes of eosinophilia. Clinical manifestations of HES are highly variable, ranging from asymptomatic eosinophilia to severe tissue damage and end-organ failure. Case presentation We herein present the case of a 65-year-old female with a 38-year history of hemodialysis who presented with lower leg pain, fever, skin eruption with leg edema, and diarrhea. Two months before admission, she underwent placement of a stent made of nickel and titanium for abdominal aortic stenosis. Lower leg pain occurred during hemodialysis, followed by fever, pedal edema with skin eruption, and diarrhea. Gastrointestinal endoscopy, colonoscopy, and biopsy histopathology revealed colitis with massive infiltration of eosinophils, compatible with eosinophilic gastroenteritis and colitis. The patient was treated with prednisolone at an initial dose of 40 mg daily and later reduced to 10 mg daily, after which her symptoms improved and her laboratory parameters normalized. She has not experienced a relapse after 1 year of follow-up. Conclusions Our case of HES manifested as eosinophilic gastroenteritis and colitis and was successfully treated with corticosteroids. Clinicians should consider the differential diagnosis of HES when faced with similar cases in order to effect timely and appropriate treatment.